Dapur Sehat KWT Panca Warna: Penguatan Dinamika Kelompok Wanita Tani dalam Pencegahan Stunting Berbasis Pangan Lokal Kacang Buncis di Desa Sembalun - Hayati; Muktasam; Daeva Mubarika Raisa; Mardiana Mardiana (Universitas Mataram, 2026)
Stunting is a chronic nutritional problem that requires active community involvement, particularly from women farmer groups that play an important role in household food management. This community service activity aimed to strengthen the existence and group dynamics of the Panca Warna Women Farmer Group (Kelompok Wanita Tani/KWT) in supporting stunting prevention through the utilization of local food resources based on green beans in Sembalun Timba Gading Village, Sembalun District, East Lombok Regency. The implementation was carried out through three stages: preparation and coordination, socialization on strengthening the existence and dynamics of the women farmer group, and socialization on stunting prevention and the utilization of local green beans as a nutritious food source. The materials covered the concept of stunting, the First 1,000 Days of Life, the concept of Diverse, Nutritious, Balanced, and Safe (B2SA) food, the role of women farmer groups as agents of change, group dynamics, and the nutritional potential of green beans as a local food resource. Evaluation was conducted using pre-tests and post-tests. The results showed that the average percentage of correct answers increased from 73% in the pre-test to 91.5% in the post-test, indicating an average improvement of 18.5%. The highest increase was observed in the aspect of group business management, which improved by 40%. These findings demonstrate that the socialization program effectively enhanced participants’ knowledge and strengthened the role of the women farmer group as a driver of local food education and community-based stunting prevention.